Production of the metabolites with antibacterial activity and its mechanism of endophyte Paenibacillus polymyxa Y4 against Staphylococcus aureus - Yan-Yu Hu; Shu-Qi Chen; Zhen-Xing Tang; Zhong-Bao Jiang; Wen-Qing Xia; Hui-Yang Shen; Qian-Yu Wang; Yue Wang; Meng-Yun Wang; Lu-E Shi (Food Bioscience, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Self-powered photosynthetic microalgae hydrogel for bioelectric–oxygen–hydrogen–ATP and vesicular Nanomedicine–synergized osteoarthritis mitigation - Yu-Wen Tseng; Pei-Wei Weng; Hsien-Tsung Lu; Chia-Hung Liu; Yan-Ting Chen; Shen-Han Wu; Hieu Trung Nguyen; Andrew E.-Y. Chuang (Chemical Engineering Journal, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Genome-wide identification and characterization of R2R3-MYB gene family and functional exploration on MYB34 in Isatis indigotica - Yan Dong; Yan Zhang; Kaiwei Qin; Jiamin Kang; Lanying Cai; Xin Li; Xue Tang; Miao Lu; Tian’e Gao; Tao Li (Plant Biosystems, 2025)

Magnetite-augmented sulfur-siderite autotrophic denitrification: Deep nitrogen removal at ultra-low HRT from lab to pilot scale - Jiale Sun; Haoyong Li; He Dong; Lu Liu; Chunyv Zhou; Ziwen Du; Yan Dang; Dawn E. Holmes (Water Research, 2025)

Precise fabrication of biochar nanosheets through CoAl-layered double hydroxide template-oriented effect for water decontamination via peroxymonosulfate activation - Chu-Chu Hu; Qi-E Zhang; Si-Cheng Hu; Si-Qin Guo; Yong-Xin Xin; Yan Pan; Jin-Gang Yu; Limin Lu; Guo-Qing Zhao (Journal of Environmental Management, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Microbial taxa and interactions can predict lignin mineralization in soil at continental scale - Wenjuan Yu; Wenjuan Huang; Kenneth E. Hammel; Yan Li; Shanshan Zhang; Bo Yi; Vitaliy I. Timokhin; Chaoqun Lu; Adina Howe; Samantha R. Weintraub-Leff; Steven J. Hall (Soil Biology and Biochemistry, 2025)

Towards healthy sleep environments: Ambient, indoor, and personal exposure to PM2.5 and its implications in children's sleep health - Yalin Lu; Ming Yan; Simi Hoque; Ignacio E. Tapia; Nan Ma (Environmental Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Assembly and variation of root-associated microbiota of rice during their vegetative growth phase with and without lindane pollutant - Jiayin Feng; Ashley E. Franks; Zhijiang Lu; Jianming Xu; Yan He (Soil Ecology Letters, 2021)

EPG-recorded Feeding Behaviors Reveal Adaptability and Competitiveness in Two Species of Bemisia tabaci (Hemiptera: Aleyrodidae) - Shao-hua Lu; Jing-jing Li; Run-e Bai; Feng-ming Yan (Journal of Insect Behavior, 2021)

Molecular, functional, and cellular alterations of oocytes and cumulus cells induced by heat stress and shock in animals - Sameh A. Abdelnour; Chun-Yan Yang; Ayman A. Swelum; Mohamed E. Abd El-Hack; Asmaa F. Khafaga; Mohamed Abdo; Jiang-Hua Shang; Yang-Qing Lu (Environmental Science and Pollution Research, 2020)

Nitric Oxide Critically Regulates Purkinje Neuron Dendritic Development Through a Metabotropic Glutamate Receptor Type 1–Mediated Mechanism - Vasiliki Tellios; Matthew J. E. Maksoud; Yun-Yan Xiang; Wei-Yang Lu (The Cerebellum, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Overexpression of OsIAAGLU reveals a role for IAA–glucose conjugation in modulating rice plant architecture - Xiao-lu Yu; Hai-yan Wang; David W. M. Leung; Zhi-dan He; Jian-jun Zhang; Xin-xiang Peng; E-e Liu (Plant Cell Reports, 2019)

Estrogen deficiency compromised the β2AR-Gs/Gi coupling: implications for arrhythmia and cardiac injury - Hongjian Hou; Zhiwei Zhao; Jeremiah Ong’achwa Machuki; Lin Zhang; Yan Zhang; Lu Fu; Jinxia Wu; Yuyu Liu; Sian E. Harding; Hong Sun (Pflügers Archiv - European Journal of Physiology, 2018)

Genomic structure of the native inhabitants of Peninsular Malaysia and North Borneo suggests complex human population history in Southeast Asia - Chee-Wei Yew; Dongsheng Lu; Lian Deng; Lai-Ping Wong; Rick Twee-Hee Ong; Yan Lu; Xiaoji Wang; Yushimah Yunus; Farhang Aghakhanian; Siti Shuhada Mokhtar; Mohammad Zahirul Hoque; Christopher Lok-Yung Voo; et al. (Human Genetics, 2018)

Antibacterial mechanism of high-mobility group nucleosomal-binding domain 2 on the Gram-negative bacteria Escherichia coli - Heng Li; Xiao-fei Shen; Xin-e Zhou; Yan-e Shi; Lu-xia Deng; Yi Ma; Xiao-ying Wang; Jing-yu Li; Ning Huang (Journal of Zhejiang University-SCIENCE B, 2017)

Nonlinear fault detection threshold optimization method for RAIM algorithm using a heuristic approach - Pan He; Gang Liu; Chun Tan; Yan-e Lu (GPS Solutions, 2016)

Internal loop photo-biodegradation reactor used for accelerated quinoline degradation and mineralization - Ling Chang; Yongming Zhang; Lu Gan; Hua Xu; Ning Yan; Rui Liu; Bruce E. Rittmann (Biodegradation, 2014)

Improved yield and Zn accumulation for rice grain by Zn fertilization and optimized water management - Yu-yan Wang; Yan-yan Wei; Lan-xue Dong; Ling-li Lu; Ying Feng; Jie Zhang; Feng-shan Pan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Characterization of 68Zn uptake, translocation, and accumulation into developing grains and young leaves of high Zn-density rice genotype - Chun-yong Wu; Ying Feng; Md. Jahidul Islam Shohag; Ling-li Lu; Yan-yan Wei; Chong Gao; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cellular and organ level localization of maltose in maltose-excess Arabidopsis mutants - Yan Lu; Jon M. Steichen; Sean E. Weise; Thomas D. Sharkey (Planta, 2006)